2020
DOI: 10.24093/awej/vol11no2.24
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Sheltered Instructional Observation Protocol (SIOP) Model in the Saudi Classroom: EFL Teachers’ Perspectives

Abstract: This study evaluates the Sheltered Instruction Observation Protocol (SIOP) model and its application in the Saudi classroom from the English language teachers' perspective. The study used a descriptive study design, with a selected sample of 300 male and female English language teachers from elementary and middle schools. The research conducted a group-wide comparison using the Statistical Package for Social Sciences (SPSS). Findings illustrate that educational qualification, career status, job experience and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Those demands need to be taken into consideration when teaching ELLs so as to provide them with the best knowledge. Hence, the number of English language learners is growing in Saudi Arabia (Al Fadda, 2020). Yet, their academic proficiency level is showing no progress (Al Fadda, 2020).…”
Section: The Learning Needs Of Ellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those demands need to be taken into consideration when teaching ELLs so as to provide them with the best knowledge. Hence, the number of English language learners is growing in Saudi Arabia (Al Fadda, 2020). Yet, their academic proficiency level is showing no progress (Al Fadda, 2020).…”
Section: The Learning Needs Of Ellsmentioning
confidence: 99%
“…Hence, the number of English language learners is growing in Saudi Arabia (Al Fadda, 2020). Yet, their academic proficiency level is showing no progress (Al Fadda, 2020). It is suggested that the usage of the SIOP model will significantly enhance the ELLs academic performance (McIntyre et al, 2010).…”
Section: The Learning Needs Of Ellsmentioning
confidence: 99%
See 1 more Smart Citation